Warning symptoms before major myocardial infarction. - Stowers, M (1970)
One hundred and eighty patients in hospital with proven myocardial infarction were questioned during their recovery about any unusual symptoms they experienced during the two months before the diagnosis of infarction. One hundred and twenty-two (68%) admitted to such symptoms. Ninety-nine (55% of the total) said they had experienced either the onset or an intensification of attacks of pain in the chest. Twenty-three (13%) described other symptoms, particularly tiredness or breathlessness. Of the 122 patients with prodromal symptoms, only 36 consulted their doctors, and of these 14 received only reassurance. The fact that such a high proportion of patients experience prodromal symptoms gives ground for hope that myocardial infarction might be averted in many instances. To achieve this, doctors need to be better trained to recognize the early symptoms of coronary heart disease, and, above all, further research is urgently needed to establish an effective prophylactic regimen. Once these goals have been achieved, there will be a strong case for educating the public to recognize coronary symptoms.